Lymphadenectomy after a positive sentinel node biopsy in patients with cutaneous melanoma. A systematic review - Maribel L. Da Cunha Cosme; Juan F. Liuzzi Samaterra; Saul A. Siso Cardenas; José I. Chaviano Hernández (BMC, 2021)
Abstract Complete lymph node dissection (CLND) following a positive sentinel lymph node biopsy (SLNB) has been the standard treatment for years. However, there is increasing evidence that CLND could be omitted. Approximately 80% of patients with a positive sentinel node biopsy do not have additional nodal involvement; in these contexts, the SLNB could be diagnostic and therapeutic. However, in this group of patients, the therapeutic effect of CLND is unclear. A systematic search was performed in EMBASE and MEDLINE (PubMed), for studies published between January 1, 2014 and December 31, 2019. Studies were included when they compared immediate CLND and observation after a positive sentinel node. The outcomes of interest were: Overall Survival (OS), melanoma-specific survival (MSS), and disease-free survival (DFS). Eleven studies met the inclusion criteria. Two randomized clinical trials reported no differences in OS or MSS when complete lymph dissection was compared with observation alone. An increase in regional relapse was observed in the CLND group, and in one randomized controlled trial (RCT) the rate of disease-free survival was superior in those patients. Most populations in both RCTs had low sentinel lymph node biopsy (SLNB) metastatic deposits, and head and neck melanomas were not included or underrepresented. When CNLD was omitted, an active surveillance protocol was carried out. The evidence supports that CLND in SLNB positive patients does not confer a survival benefit. Sentinel tumor burden, localization of primary tumor, and feasibility of active surveillance should be taken into account in treatment decisions.